Pentingnya Kesadaran Antarbudaya dan Kompetensi Komunikasi Antarbudaya dalam Dunia Kerja Global - Amia Luthfia (Bina Nusantara University, 2014)
In this global era, communication, interaction and intercultural encounters happen every second. Technology expands the ability of people throughout the world to connect to each other for vacation or for business purpose. Intercultural communication skills will be critical necessity. The ability to work in multicultural workforce and interact with people from other cultures, often in other languages, is inherent to the success of a multinational business. Effective global enterprise communication skills are the backbone that supports the transaction of business around the world. This paper highlights the importance of intercultural awareness and the need for intercultural communication competence training for all local and multinational companies. Therefore, intercultural cooperation and synergy become an important aspect in this era. Companies that have intercultural competence will be able to succeed and sustain success in global business.